CAREER GUIDANCE WORK WITH STUDENT YOUTH AT THE EDUCATIONAL AND SCIENTIFIC INSTITUTE OF EDUCATION DEVELOPMENT OF NAU - Petrovska, Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article highlights the current problem of career guidance work. The peculiarities of career guidance activities were revealed and the impact of career guidance events regarding the choice of a future profession was confirmed.